Acquired platelet GPVI receptor dysfunction in critically-ill patients with sepsis - Weiss, Lukas Johannes; Manukjan, Georgi; Pflug, Annerose; Winter, Nadine; Weigel, Mathis Leonard; Nagler, Nils; Kredel, Markus; Lam, Thien-Tri; Nieswandt, Bernhard; Weismann, Dirk; Schulze, Harald (Blood, 2021)
GPVI, the platelet immunoreceptor tyrosine activating motif (ITAM) receptor for collagen plays a striking role on vascular integrity in animal models of inflammation and sepsis. Understanding ITAM-receptor signaling defects in humans suffering from sepsis may improve our understanding of the pathophysiology, especially during disease onset. In a pilot study, platelets from fifteen septic patients were assessed consecutively at day of admission, day 5-7 and the day of ICU-discharge, and subjected to comprehensive analyses by flow cytometry, aggregometry and immunoblotting. Platelet function was markedly reduced in all patients. The defect was most prominent after GPVI stimulation with collagen-related peptide. In 14/15 patients GPVI-dysfunction was already present at time of ICU admission, considerably before the critical drop in platelet counts. Sepsis platelets failed to transduce the GPVI-mediated signal to trigger tyrosine phosphorylation of Syk kinase or LAT. GPVI deficiency was in part inducible in platelets of healthy donors through co-incubation in whole blood, but not in plasma from sepsis patients. Platelet aggregation upon GPVI stimulation increased only in those patients whose condition ameliorated. As blunted GPVI signaling occurred early at sepsis onset this defect could be exploited as an indicator for early sepsis diagnosis, which needs to be confirmed in prospective studies.